PKCα Modulates Epithelial-to-Mesenchymal Transition and Invasiveness of Breast Cancer Cells Through ZEB1 - Llorens, María Candelaria; Rossi, Fabiana Alejandra; García, Iris Alejandra; Cooke, Mariana; Abba, Martin C.; Lopez-Haber, Cynthia; Barrio-Real, Laura; Vaglienti, María Victoria; Rossi, Mario; Bocco, José Luis; Kazanietz, Marcelo G.; Soria, Gastón (Frontiers in Oncology, 2019)
ZEB1 is a master regulator of the Epithelial-to-Mesenchymal Transition (EMT) program. While extensive evidence confirmed the importance of ZEB1 as an EMT transcription factor that promotes tumor invasiveness and metastasis, little is known about its regulation. In this work, we screened for potential regulatory links between ZEB1 and multiple cellular kinases. Exploratory in silico analysis aided by phospho-substrate antibodies and ZEB1 deletion mutants led us to identify several potential phospho-sites for the family of PKC kinases in the N-terminus of ZEB1. The analysis of breast cancer cell lines panels with different degrees of aggressiveness, together with the evaluation of a battery of kinase inhibitors, allowed us to expose a robust correlation between ZEB1 and PKCα both at mRNA and protein levels. Subsequent validation experiments using siRNAs against PKCα revealed that its knockdown leads to a concomitant decrease in ZEB1 levels, while ZEB1 knockdown had no impact on PKCα levels. Remarkably, PKCα-mediated downregulation of ZEB1 recapitulates the inhibition of mesenchymal phenotypes, including inhibition in cell migration and invasiveness. These findings were extended to an in vivo model, by demonstrating that the stable knockdown of PKCα using lentiviral shRNAs markedly impaired the metastatic potential of MDA-MB-231 breast cancer cells. Taken together, our findings unveil an unforeseen regulatory pathway comprising PKCα and ZEB1 that promotes the activation of the EMT in breast cancer cells.